Knockdown of MAPK14 inhibits the proliferation and migration of clear cell renal cell carcinoma by downregulating the expression of CDC25B - Junlong Liu; Xiuyue Yu; Hongyuan Yu; Bitian Liu; Zhe Zhang; Chuize Kong; Zhenhua Li (Cancer Medicine, 2020)
Abstract Mitogen‐activated protein kinase 14 (MAPK14), which plays an important role in DNA damage and repair, is activated by various environmental stress and proinflammatory cytokines. It is highly active in a variety of tumors, acting as a tumor promoter or suppressor, but its role in clear cell renal cell carcinoma (ccRCC) has not been elucidated. Cell division cycle 25B (CDC25B) is involved in cell cycle regulation and is highly expressed in many malignant tumors. The transcription levels of MAPK14 and CDC25B in 72 pairs of ccRCC and adjacent healthy tissues from the cancer genome atlas database and the protein expression levels in 66 pairs of clinical samples were analyzed in this study. After MAPK14 was knocked down by small interfering RNA (siRNA), P‐MAPK14 and CDC25B protein levels decreased. Subsequently, Western blot and co‐immunoprecipitation demonstrated that P‐MAPK14 could bind to CDC25B, potentially maintaining its stability. The proliferation and migration of ccRCC cell lines were suppressed by siRNA knockdown of MAPK14, however, that could be partially reversed by the overexpression of CDC25B. These results suggest that downregulation of MAPK14 and P‐MAPK14 could inhibit the proliferation and migration of ccRCC by downregulating CDC25B.